AWARENESS REGARDING DIABETES AND ITS MANAGEMENT AMONGST PATIENTS VISITING TERTIARY CARE HOSPITALS AND ITS IMPACT ON GLYCEMIC CONTROL: Diabetes and its Management Awareness - Khan, Anum; Arshad, Abdul Rehman; Farooq, Asif; Raashid, Sheharyar (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess factors affecting disease awareness in diabetics, and its association with glycemic control. Study Design: Cross-sectional analytical study. Place and Duration of Study: Department of Medicine, Pak Emirates Military Hospital Rawalpindi from Jan to Apr 2019. Methodology: Outdoor patients with type-II diabetes mellitus were selected using a consecutive sampling technique. Disease awareness was assessed with a modified Diabetes Knowledge Questionnaire, with scores >70% considered satisfactory. Recent HbA1c levels were used to determine glycemic control (<7% reflecting good glycemic control). Demographic data, including age, gender, level of education, residence, duration of diabetes, mode of treatment, smoking status and co-existing hypertension, were also recorded. Results: There were 212 patients with equal gender distribution and mean age of 55.90 ± 11.96 years. Of these, 117 (55.18%) lived in rural areas, 77 (36.32%) were educated, 34 (16.03%) were smokers and 121 (57.07%) had co-existing hypertension. The mean duration of diabetes was 81.72 ± 71.67 months (range 3-360 months) and mean HbA1c levels were 9.55 ± 2.56%. Higher HbA1c levels were associated with poorer DKQ scores. The level of education and the duration of diabetes significantly predicted DKQ scores. Conclusion: Lack of disease awareness leads to poor glycemic control. Better education and longer disease duration impact the understanding of diabetes.